WAHDAH AL-WUJUD IBN ARABI DALAM IMAJINASI KREATIF HENRY CORBIN - Raha Bistara (Academic Journal of Islamic Principles and Philosophy, 2020)
This article aims to explain the idea of wahdah al-wujudIbn Arabi in the frame of Henry Corbin’s creative imagination. Wahdah al-wujud is still being debated among philosophers. Some of them say wahdah al-wujud is the same as pantheism and panenteism and some say its not with both. With a descriptive qualitative method and based on library research, this study shows that creative imagination (theophysical imagination) is a form of God revealing himself, showing himself, to himself by distinguishing himself with its hidden existence. This creation is the same as the appearance of God (tajalli ilahi). In this creation there is no concept of creation ex nihilo(creation out of nothing), this creation already existed from God itself through the tanaffus process. Creative imagination as a theophanic is a process of creation not of nothing or something different from Himself, but from His fundamental form that is hidden in His own form without the existence of a creative imagination that is difficult to realize God in the midst of human life.